Normative data for the Digit Symbol Substitution Test in a population-based sample aged 65–79 years: Results from the German Health Interview and Examination Survey for Adults (DEGS1). (30th November 2018) - Gaertner, Beate; Wagner, Michael; Luck, Tobias; Buttery, Amanda K.; Fuchs, Judith; Busch, Markus A.
ABSTRACT: Objective: To provide normative data for the Digit Symbol Substitution Test (DSST) of the Wechsler Adult Intelligence Scale, 3rd edition (WAIS-III) in a population-based sample of community-dwelling older adults in Germany according to age, sex, and level of education. Method: The sample comprised 1385 participants aged 65–79 years from the nationwide representative 'German Health Interview and Examination Survey for Adults' (DEGS1, 2008–2011). Participants with known cognitive impairment or dementia, other medical conditions affecting cognition, or currently using psychotropic drugs were excluded. Educational level was categorized as low, medium, and high according to the Comparative Analyses of Social Mobility in Industrial Nations (CASMIN) scale. Normative values for the DSST according to age, sex, and level of education were estimated by multiple linear regression using population weights. Results: Mean age was 71.1 years, 48.6% were men and low, medium, and high education levels were 62.8, 24.6, and 12.6%, respectively. Younger age, female sex, and higher level of education were significantly associated with higher DSST scores. Regression-based normative data for the DSST is provided according to age, sex, and level of education. In addition, a normative score calculator is provided. Conclusions: These are the first age-, sex-, and education-specific normative data for older individuals for the DSST of the WAIS-III in Germany. These normative data will enable future population-level analyses on impaired cognitive function according to DSST.